Strategic Issues in Air Transport - Abeyratne, Ruwantissa. author. aut Link
XIV, 426 p.
Keywords: There are broadly four strategic issues in aviation: safety; security; environmental protection; and sustainability in air transport. These issues will remain for a long time as key considerations in the safe, regular, efficient and economic development of air transport. Within these four broad categories come numerous subjects that require attention of the aviation industry as well as the States. In six chapters, this book engages in detailed discussions on these subjects as they unravelled in events of recent years. The issue of safety is addressed first, following an introduction of the regulatory regime covering the four issues. Within the area of safety, the book covers such areas as safety management systems, safety and aeromedicine, safety and meteorology, the use of airspace, unmanned aircraft systems and safety oversight audits. In the security area, subjects covered include cyber terrorism, the integrity of travel documents, full body scanners, civil unrest and aviation, the suppression of unlawful acts on board aircraft and the financing of terrorism. The chapter on the environment focuses mainly on climate change - particularly on carbon credits, market based measures, the carbon market and emissions trading schemes and their effect on air transport. Finally, the chapter on sustainability discusses in detail market access along with such issues as slot allocation, open skies, the use of alternative fuels as an economic measure and corporate foresight. The concluding chapter wraps up with a discussion on where air transport is headed. .